"Association between Periodontal Disease and Elevated C-reactive Protein in Acute Myocardial Infarction Patients " - G. Radafshar; B. Shad; M. Mirfeizi (Tehran University of Medical Sciences, 2006)
Statement of problem: Periodontal disease (PD) has been linked to adverse cardiovascular events by unknown mechanisms. C-reactive protein (CRP) is a prognostic marker for cardiovascular disease, with reported elevated serum levels during PD. Purpose: The aim of the present study was to evaluate the association between PD and higher CRP levels in the serum of acute myocardial infarction (AMI) patients. Materials and Methods: In this cross-sectional study, periodontal examinations and CRP serum levels were measured in 51 Q-wave and non-Q-wave AMI patients. All assessments were made during index hospitalization and within 72 hours of symptom onset. The patients were divided into two groups based on the presence or absence of PD and were frequency matched for sex, body mass index, smoking and traditional risk factors of cardiovascular disease. Using t-test, the results were compared between the two groups. Results: The prevalence of PD was high in patients with AMI (70.5%). AMI cases who had PD, showed significantly (P